Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.15406/iratj.2020.06.00211
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of continuous cover forestry expansion under the influence of Global warming

Abstract: Planet Earth faces the problem of global warming. Recent research on the dynamics of the CO 2 concentration in the atmosphere has shown how reductions of global industrial emissions of CO 2 can solve a large part of the global warming problem. However, there are more control options available. Our world is covered by large areas of primary (natural) forests that are almost not managed at all. They do not contribute very much to the net absorption of CO 2 . Parts of these natural forests may be transformed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The results from the parameter estimations are found in (Tables 1 & 2). In case the industrial emissions would be constant and equal to f c , then in CO 2 equilibrium, x c , equation ( 6) is satisfied, which leads to (7).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from the parameter estimations are found in (Tables 1 & 2). In case the industrial emissions would be constant and equal to f c , then in CO 2 equilibrium, x c , equation ( 6) is satisfied, which leads to (7).…”
Section: Methodsmentioning
confidence: 99%
“…If the relative weight of the utility of the climate increases, the optimal area of natural forests that should be transformed to managed continuous cover forests increases. Several concrete results were reported in this area by Lohmander [7,8].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies and results concerning CO 2 dynamics and rational forest management are found in Lohmander (2020a, 2020b and 2020c). [5][6][7] Countries close to the equator mostly have much larger and more dramatic forest fires than countries closer to the poles. Table 1, shows this very clearly, where it is found that the European countries in the south: Italy, France, Portugal and Spain, denoted "IFPS", on average, together, have the average yearly burned area of 313 400 hectares.…”
Section: Introductionmentioning
confidence: 99%